Implicaç\~oes dos novos regimes fiscais no financiamento da educaç\~ao pública - Camillo de Moraes Bassi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This text for discussion addresses the implications of the new tax regimes - Union and states - in the financing of public education. It adopts the disaffection of taxation as the northern implications, and concludes that the changes generated a less cooperative, more restrictive in terms of resources, and seemingly divergent federal principles. The changes also imposed an overload on municipalities that extrapolate their tax capacity.
Keywords: H68; H52; I22; 330; new tax regimes; financing; public education